Comparative safety review of recommended, first-line single-tablet regimens in patients with HIV. Issue 11 (2nd November 2021) - Ciccullo, Arturo; Baldin, Gianmaria; Putaggio, Cristina; Di Giambenedetto, Simona; Borghetti, Alberto
ABSTRACT: Introduction Different single-tablet regimens (STRs), containing one or two nucleoside reverse transcriptase inhibitors (NRTIs) plus an anchor drug, are available for the use in naïve, HIV-infected patients. Despite some restrictions in the use of particular regimens in certain situations (e.g., HBV coinfection), International guidelines do not provide indications to prefer any regimen over others concerning the tolerability profile. We aimed to assess advantages and disadvantages of the most prescribed STRs. Areas covered An extensive review of articles published in English language was conducted on PubMed, looking for evidence about STRs in naïve, HIV-infected population. Safety outcomes of registrational trials were assessed, giving priority to studies directly comparing STRs included in our research (abacavir/lamivudine/dolutegravir, tenofovir alafenamide/emtricitabine/bictegravir, lamivudine/dolutegravir, tenofovir alafenamide/emtricitabine/darunavir/cobicistat, tenovofir disoproxil fumarate/lamivudine/doravirine). Data from cohort studies and meta-analyses were also assessed, extrapolating the main evidence about the combinations of interest. Expert opinion Integrase inhibitors (InsTIs)-based regimens have few interruptions for adverse events and few drug-related adverse events, with tenofovir alafenamide/emtricitabine/dolutegravir and lamivudine/dolutegravir being the most tolerable ones. However, neuropsychiatric adverse events and metabolic issues could prompt the alternative use of darunavir or doravirine-based combinations, even if a superior safety profile of these combinations over InSTIs has yet to be demonstrated.